Basics Design 07 Grids - Ambrose, Gavin (Basics design 07., 2008)
Focuses on the construction and ordering of the page and screen through the use of the grids. This book explores not only how to construct grids, but, more fundamentally, why a designer should construct grids at all. It also explores key areas of grid design through a series of case studies, juxtaposed by key creative 'basics.